-2-5b+8b=-8(-3-6b)-5(8+6b)

Simple and best practice solution for -2-5b+8b=-8(-3-6b)-5(8+6b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-5b+8b=-8(-3-6b)-5(8+6b) equation:


Simplifying
-2 + -5b + 8b = -8(-3 + -6b) + -5(8 + 6b)

Combine like terms: -5b + 8b = 3b
-2 + 3b = -8(-3 + -6b) + -5(8 + 6b)
-2 + 3b = (-3 * -8 + -6b * -8) + -5(8 + 6b)
-2 + 3b = (24 + 48b) + -5(8 + 6b)
-2 + 3b = 24 + 48b + (8 * -5 + 6b * -5)
-2 + 3b = 24 + 48b + (-40 + -30b)

Reorder the terms:
-2 + 3b = 24 + -40 + 48b + -30b

Combine like terms: 24 + -40 = -16
-2 + 3b = -16 + 48b + -30b

Combine like terms: 48b + -30b = 18b
-2 + 3b = -16 + 18b

Solving
-2 + 3b = -16 + 18b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-18b' to each side of the equation.
-2 + 3b + -18b = -16 + 18b + -18b

Combine like terms: 3b + -18b = -15b
-2 + -15b = -16 + 18b + -18b

Combine like terms: 18b + -18b = 0
-2 + -15b = -16 + 0
-2 + -15b = -16

Add '2' to each side of the equation.
-2 + 2 + -15b = -16 + 2

Combine like terms: -2 + 2 = 0
0 + -15b = -16 + 2
-15b = -16 + 2

Combine like terms: -16 + 2 = -14
-15b = -14

Divide each side by '-15'.
b = 0.9333333333

Simplifying
b = 0.9333333333

See similar equations:

| 6(-2)-y=-18 | | 6y=49-y | | 2a+a=39 | | 7w=w+18 | | -7v+6=-36 | | 6(3)-y=-18 | | 2.4=02 | | a+1-2a-1E+1=2 | | y=3x+6x-9 | | 8x-15y=0 | | a+b-(ab)=1 | | 6(2)-y=-18 | | ba=a+b+1 | | 3(c+3)+8=-10 | | 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a | | 7x-3x+9=29 | | -6x+17=8x+5 | | 5x-19=-7 | | 109-x=167 | | 3+5z= | | 6n-2=-68 | | -2.4k=42 | | b+5-6=18 | | 95+x=x | | 2x=-21+3 | | -0.54=.36m | | 195/200 |

Equations solver categories